Sensor detection of termites / Suraya Ashyikin Rashid and Dzulkarnaen Ismail - Rashid, Suraya Ashyikin; Ismail, Dzulkarnaen (2023)
Defects, if left untreated, along with poor and ineffective building maintenance, will undoubtedly lead to more damage and costly repair work. To some, building maintenance is a difficult and costly procedure, but if done correctly, it may save money as well as potentially extend the life of the structure. Unfortunately, the building’s maintenance is still lacking. The cost of repairing a building that has already been damaged due to a termite attack will be incurred by the client if the building is left untreated. The research objectives of this study are to create Sensor Detection of Termites design ideas, assemble the prototype from the improvised design of Sensor Detection of Termites, assess the performance of Sensor Detection of Termites prototype, and demonstrate entrepreneurial skills in proposing Sensor Detection of Termites prototype to be marketable. This research involves secondary data collection to learn how infrared thermography can contribute to find defects in construction industry.